PENGARUH TEKNIK KONSERVASI SECARA VEGETATIF TERHADAP EROSI TANAH PADA BUDIDAYA KENTANG (Solanum tuberosum) DAN KUBIS (Brassica oleracea) DI DESA KASIMPAR, DAS SERAYU HULU - , Esti Rahayu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kasimpar village is one of the villages in the upstream of Serayu Watershed that have high erosion due to the exploitation of agricultural land use. Soil conservation techniques necessary to reduce erosion and its impacts. This study aims to (1) analyze the best vegetative soil conservation technique to decrease erosion (2) analyze the best vegetative soil conservation technique to decrease organic Carbon loss (3) analyze the best vegetative soil conservation technique to increase the yield of potato and cabbage . This research was conducted during the growing season, ie from December 2013 to March 2014. The method used to determine the amount of soil erosion is an experimental method by making erosion plots. The number of erosion plots is 22 plots installed on slope 45 o and 25 o . Each plot was treated differently by using a combination of primary vegetation and ground cover vegetation or organic mulch. The main vegetations used are potato and cabbage. Ground cover plants are used in the form of sweet potato, red beans, corn stalk mulch, and elephant grass mulch. The amount of organic Carbon loss is known through laboratory by spectrophotometric method, while agricultural output is calculated after harvest. The results of this study show that the best conservation technique on potato cultivation is using sweet potato. Erosion decreased 90,88% on slope 45 o , whereas on slope 25 o it decreased 85,18%. Organic Carbon loss decreased 90,23% on slope 45 o , whereas on slope 25 o it decreased 25,76%. The yield increased 150% on slope 45 o , whereas on slope 25 o it increased 216,67%. In other hand, the best conservation technique on cabbage cultivation is using corn stalks mulch. Erosion decreased 94,49% on slope 45 o , whereas on slope 25 o it decreased 91,46%. Organic Carbon loss decreased 88,84% on slope 45 o , whereas on slope 25 o it decreased 89,36%. The yield increased 21,69% on slope 45 o , whereas on slope 25 o it increased 13,33%.